Retenção na fonte do Imposto de Renda e suas balizas constitucionais - Melo, Felipe Azzi Assis de (2021)
The purpose of our essay is to analyze Constitutional and legal limits applicable when electing the taxable person, specifically when such election is made by using the withholding tax technique. We focused exclusively on the Income Tax, as we understand this is the tax in which the withholding tax mechanism is most frequently used. Proper identification of the taxable person is a topic that deserves a wide number of research papers and judicial decision in Brazil. The concern is only natural, as the taxable person holds a fundamental role in collecting the tax credit. In this scenario, tax withholding is a commonly used mechanism, in which the tax responsible (payer source) must pay partially or entirely the tax credit that would be naturally due by the receiver. Tax withholding is a mechanism commonly adopted by the administrators seeking a better efficiency in tax collection activities, reducing tax evasion and promoting fair competition. The withholder, even if not bearing the economic burden of the tax, is frequently involved in complex legislation, incurring in compliance costs and possibly suffering tax assessments, what may harm its’ constitutional rights. Hence, our purpose is to analyze the constitutional guidelines that must be observed by the legislators when creating the tax withholding mechanism